Investment Objective, Investment Portion and Risk Taking Capacity of the Respondents in Agricultural Commodity Market of Narmadapuram Division with Reference to Soyabean and Wheat Crop (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Narmadapuram division consists of Harda, Betul and Hoshangabad district and they are chosen for the present study as per stratified random sampling. The said districts were selected because Soyabean and Wheat crop are cultivated at large while comparing with other districts. The study pertaining about the commodity market covers the period of 3 years (2014-2016). In the present study the investment objectives, investment portion and risk taking capacity of the respondents in agricultural commodity market of Narmadapuram division.